Comparative Evaluation of the Proximate, Phytochemical and Antioxidant Properties of Selected Leafy Vegetables (Bitter, Pumpkin and Spinach Leaves) (Lafia Journal of Scientific and Industrial Research, 2024)
The study is aimed at comparative evaluation of the proximate, phytochemicals and antioxidant properties of three leafy vegetables (V. amygdalina, Spinacia oleracea and Telfairia occidentalis).The study was carried out using standard analytical procedures. The proximate analysis revealed highest percent moisture (5.08±0.13%), crude protein (19.69±0.87%), carbohydrate  (38.31± 1.42 %) and metabolizable energy (244.24±3.82 KJ/100 g) in pumpkin,  highest percent ash (15.20± 0.86 %), %) and crude fat contents (8.30±0.18 %) in spinach, while bitter leaf recorded  the highest percent crude fibre (20.01 ± 1.20%).  The phytochemical analysis revealed the presence of flavonoid, saponin, alkaloid, tannin and phenol which ranged from 8.67±0.11 mg/100 g to 18.98± 0.15mg/100 g, 0.9±0.00 mg/100 g to 1.21± 0.10 mg/100 g, 8.87±0.21 mg/100 g to 11.65±0.68 mg/100 g, 0.81 ± 0.01 to 10.32± 1.2 mg/100 g and 1.36 ±0.01 mg to 4.24±0.01 mg/ 100 g respectively. The antioxidant activities revealed highest percent inhibition (71.20%) in bitter leaf. However, based on the analysis of variance on the results obtained, the study revealed that there were significant differences in most of the analyzed parameters at P ≥ 0.05. Therefore, this study inferred that  the nutritional and phytochemical contents of the leafy vegetables samples varied significantly and their consumption in a diet  will be responsible for maintaining good health and proper functioning of the body system.